2006
DOI: 10.1002/joc.1454
|View full text |Cite
|
Sign up to set email alerts
|

Detecting trends in tropical rainfall characteristics, 1979–2003

Abstract: Abstract:Analyses of two state-of-the-art, blended space-based and ground-based global rainfall data sets from the Global Precipitation Climatology Project (GPCP) and the Climate Prediction Center Merged Analysis Product (CMAP) reveal that there was a significant shift in the probability distribution functions of tropical rainfall during the period 1979-2003. This shift features a positive trend in the occurrence of heavy (top 10% by rain amount) and light (bottom 5%) rain events in the tropics during 1979-200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
105
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 23 publications
10
105
0
Order By: Relevance
“…These results are consistent with Ronchail (1996) who finds a similar pluriannual variability in Bolivia and with Marengo and Nobre (2001) and Marengo (2004) who show opposite long-term evolutions in the north and south of the Brazilian AB. Also Lau and Wu (2006) describe a similar spatio-temporal pattern, with an increase in the annual rainfall along the tropical Andes, whereas the annual rainfall decreases in the eastern and southern parts of the Amazon, between 1979Amazon, between -1990Amazon, between and 1991Amazon, between -2002. However, our study yields some insights into the seasonality of the pluriannual rainfall evolution.…”
Section: Interannual Variabilitymentioning
confidence: 60%
“…These results are consistent with Ronchail (1996) who finds a similar pluriannual variability in Bolivia and with Marengo and Nobre (2001) and Marengo (2004) who show opposite long-term evolutions in the north and south of the Brazilian AB. Also Lau and Wu (2006) describe a similar spatio-temporal pattern, with an increase in the annual rainfall along the tropical Andes, whereas the annual rainfall decreases in the eastern and southern parts of the Amazon, between 1979Amazon, between -1990Amazon, between and 1991Amazon, between -2002. However, our study yields some insights into the seasonality of the pluriannual rainfall evolution.…”
Section: Interannual Variabilitymentioning
confidence: 60%
“…The expectation is that as the water vapor content of the tropical atmosphere increases, the moisture convergence for a given amount of mass convergence is enhanced. This should increase rainfall rates in systems 47 and also an increase during warm periods of interannual variability 48 . A number of studies of land-based precipitation data have identified increasing trends in the frequency of very heavy precipitation events 2,3 .…”
Section: Detection and Attributionmentioning
confidence: 99%
“…As the water vapor content of the tropical atmosphere increases, the moisture convergence for a given amount of mass convergence is enhanced, increasing rainfall rates in systems including TCs. Using satellite data, Lau and Wu (2007) reported an increase in the occurrence of heavy rain events in the tropics during 1979̶2003. Several studies of land-based precipitation data have identified increasing trends in the frequency of very heavy precipitation events (IPCC 2007).…”
Section: Changes In the Average Rainfall Per Tcmentioning
confidence: 99%